Games in Enhancing Productive Skills for EFL Students - Munawarah, Siti; Hayati, Sifa; Fitriyani, Windi; Rahman, Erwan; Mieyrandha, Mieyrandha; Maharani, Laura Melinda; Tegar, Jonathan; Fauzi, Iwan (General English Education, 2024)
This article explores the use of games as an effective pedagogical strategy for improving EFL students' speaking and writing skills. Conducted through a literature review, the study examines various games used in language classrooms and their impact on language learning outcomes. The importance of language as a communication tool and the need to enhance students' English-speaking and writing skills are emphasized. Teachers' role in leveraging innovative game-based learning strategies is highlighted, focusing on games like Zepeto, board games, spinning wheel games, and guessing games. These games offer engaging, real-time language practice, promoting fluency, confidence, and motivation. The research method used by this study was literature reviews. Findings indicate the efficacy of these games in enhancing speaking and writing skills for the EFL students. The study underscores the value of game-based learning in making language education more enjoyable and effective. Concluding, the study advocates for the integration of game-based strategies in language classrooms to boost students' interest, engagement, and proficiency in English.